The Effect of Dragon Fruit Juice on Increasing Hemoglobin Levels in Anemic Pregnant Women - Muchtar, Asrianti Safitri; Ita Novianti,; Magfirah, (Jurnal Midwifery, 2025)
Introduction Anemia is a condition in which hemoglobin levels fall below 11 g/dL during the first and third trimesters, and below 10.5 g/dL in the second trimester. Anemia during pregnancy can reduce oxygen levels in both the mother and fetus. Pregnant women with mild anemia are at higher risk of preterm labor and delivering low birth weight infants. This study aimed to provide midwifery care through the administration of dragon fruit juice to improve hemoglobin levels in pregnant women with anemia at UPT Ulaweng Public Health Center, Bone Regency. Method: This research employed a case study approach based on the client’s needs and within the scope of midwifery practice. The care was provided using the seven-step Varney midwifery management process and documented using the SOAP format. Result: The study results indicated that after fourteen days of care, the client experienced no more dizziness, consistently consumed dragon fruit juice every morning, maintained normal vital signs, and her hemoglobin level increased from 10 g% to 11.6 g% following the 14-day intervention. Conclusion: The care provided proceeded smoothly and effectively. All findings and interventions for Mrs. “R” were documented, with no discrepancies identified.